Hubungan India Kuno dengan Asia Tenggara pada Permulaan Masehi - Utami Ferdinandus (Berkala Arkeologi, 1994)
The beginning of the relationship between Ancient India and Indonesia it's still hard to know because lack of sources that can prove the relationship clearly. In this case it needs to be questioned. Is it true that the traders from western and southern India played an important role in the early CE? This paper tries analyze the spread of the letters Kharosthi in Southeast Asia